Effect of Health Education Audio Effect of Health Education Audiovisual Media Using The Improvement of Knowledge and Attitudes in Prevention at the Health Mariat Filariasis District Sorong - Sulastri GP Tambunan (Jurnal Medika Hutama, 2020)
Abstract Most people, especially urban Sorong Mariat not have a high awareness to prevent the transmission of filariasis caused by the lack of public knowledge about health information associated with filariasis. The purpose of this study was to analyze the health education intervention using audiovisual media in the prevention of filariasis in communities Mariat in Community Health Center Mariat Sorong 2018 with the difference before and after treatment knowledge and attitudes. This type of research is semi-experimental study (Quasi Experiment) with the draft Non Randomized Control group pretest-posttest design. The population in this study is Mariat community health centers in the region of the sliding District Mariat numbered 30 people. The collected data is processed and analyzed using SPSS. The results showed there are differences in knowledge after the use of audiovisual media treatment in the prevention of filariasis in Sorong district community. Visible value of p (t test) knowledge = 0.005<0.05. Percentage to increase knowledge in the prevention of filariasis in the community health centers Mariat Sorong is 0.4282 = 0.183 (18.31%). This means that 18.31% increase knowledge in the prevention of filariasis in the community health centers Mariat Sorong. Suggested can be used by the community health centers in order to improve education in the prevention of filariasis by working with Ministry of Health Polytechnic Sorong. And for further research can use other methods such as a combination of counseling and audiovisual media for increasing knowledge.